EFEKTIVITAS KINERJA SATUAN POLISI PAMONG PRAJA DALAM PENGENDALIAN TINDAK ASUSILA DI KOTA TANJUNGPINANG - Henny Las Tiar Simatupang; Zaili Rusli. SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research aimed to analyze the effectiveness of performance Civil Service Police Unit (Municipal Police) in the control of immoral acts in Tanjungpinang. Municipal police is a government agency in control of society's ills, one of which is the act of sacrilege. This research is based on interviews and observations as initial data the authors found an issue that is the absence of strict sanctions to enforce punishment to society, a lack of Municipal Police employees and facilities are inadequate. The problem in this research is how the effectiveness of the performance of municipal police of Tanjungpinang in achieving its goal of controlling immoral acts and the factors that influence the effectiveness of the organizations performance.The writer uses the theory of organizational effectiveness by Richard M. Steers ie, productivity, adaptability, job satisfaction and the search for resources. The method used is descriptive with data collection through literature study and field studies (observation and interview) .Conclusions obtained from this research that the effectiveness of the performance of municipal police in controlling immoral acts in Tanjungpinang based adaptability and job satisfaction is quite effective. While based on the productivity and the search for resources in the category have not been effective, resulting in less effective in controlling municipal police performance immoral acts that have not run optimally .Keywords : Effectiveness, Performance, Immoral Acts.